Geomorphic Hazard Map for Spatial Planning Purposes - Taryono, T (Forum Geografi, 1996)
In the planning of spatial lay-out oriented to environmental concept, it requires the information input conneting with the condition of local environment. This condition constitutes the features characteristic of the living space which consist of natural and social environment. One of the natural environment elements, neede to the spatial lay-out planning, is the dynamis geomorphology. The process of the dynami is some times accelerated and increased by natural and anthropogenic factors. The abnormality in both acceleration and the increase will cause a natural disaster, which is based on the landscape approach it is called the geomorphologic hazard. In connection with such event thematic map of geomorphologic hazard describes the disaster susceptibility of an area. The geomorphologic hazard map is an output map whose information is obtainable from thematic map conneting with population, land use, topography, geomorphology, rainfall, hydrological data, and slope classification. Both land use and population maps desccribes the anthropogenic factors. The role of the geomorphologic hazard map, in the planning of spatial lay-out and environmental management, i.e. preventive, represive, rehabilitative, and serves as the basis for interpretation and management of living spere. By putting geomorphologic hazard into map compilation of spatial lay-out (cultural and non cultural area map) a footstep advance is the reached to guarantee human security and their treasures, and human well-being as an integral part of human living prosperity.